Clinical Features and Outcomes Analysis of Surgical Resected Pulmonary Large-Cell Neuroendocrine Carcinoma With Adjuvant Chemotherapy - Shen, Yinchen; Hu, Fang; Li, Changhui; Xu, Jianlin; Zhong, Runbo; Zhang, Xueyan; Chu, Tianqing; Han, Baohui (Frontiers in Oncology, 2020)
Abstract Objective Large-cell neuroendocrine carcinoma (LCNEC) is a rare subtype of pulmonary cancers with poor survival. Optimal adjuvant chemotherapy for resected LCNEC is controversial till now, clinical features together with the prognostic factors in LCNEC should be clarified better. Methods Clinicopathological characteristics, driven genes status (EGFR, ALK and ROS1), adjuvant chemotherapy strategy for 94 surgical resected LCNECs were extracted from digital database, tumor relapse or progression and survival were analyzed with clinical profiles. Results Driven genes mutants were scarce in LCNEC, 8.3% (4/48) samples harbored EGFR mutations, 5.8% (3/52) with ALK positive and none of ROS1 positive. A total of 44 patients suffered tumor relapse or progression during follow-up. Tumor/lymph node (N) stage, serum carcinoembryonic antigen (CEA) level before surgery, different adjuvant chemotherapy were associated with tumor relapse (P<0.05), poorer disease-free survival (DFS) appeared in N2/stage III, serum CEA positive and pemetrexed based chemotherapy (P<0.05), for overall survival (OS) analysis, the T/tumor stage, serum positive CEA/neuron-specific enolase (NSE) at baseline associated with wore OS (P<0.05). Moreover, in the multivariate analysis, N stage still acted as prognostic for DFS (P=0.019), OS differed significantly in different T stage, chemotherapy selection and serum CEA levels after adjustment (P<0.05). Conclusion Classical driven gene mutations were rare in LENEC. Tumor N stage appeared as prognostic for DFS, while serum positive CEA, different adjuvant chemotherapy strategy and T stage were independent prognostic factors for OS. Etoposide-platimun regime seemed to be a better choice which should be confirmed by further prospective investigations.